Can we attain the Millennium Development Goals in education and health through public expenditure and aid? (2003)
Looks at how good the record of public expenditure in developing countries has been in delivering two Millennium Development Goals (MDGs) targets, one each in education and health. Finds that public expenditure often has low efficiency and is biased against the poor. Notes that this has implications for the management of aid provider support of poverty reduction strategies.
Keywords: PUBLIC EXPENDITURE